A relationship between work life balance and job satisfaction among staff at Universiti Teknologi Sarawak Kampus Samarahan 2 (UiTM)./ Ammirul Yakub - Yakub, Ammirul (2018)
Job satisfaction is defined as how employees feel about their job and duties. However, although it is simple to term, realistically job satisfaction is hard and very challenging to be fulfilled. Continuous efforts are being placed by organizations to ensure their employees are content by moving towards more humanistic approach in dealing with them also identifying roles humanistic approach, and identifying roles of workers’ life than just the hours they spend in office. Although many factors have been identified as the key determinants to job satisfaction, that can only happen if employees can create a balance in their work and personal life is least studied. Thus, in view of the importance of work life balance, the research studied its role as an antecedent to job satisfaction. A survey was conducted among 119 staff at Universiti Teknologi Mara Sarawak Kampus Samarahan 2 (UiTM) and they were asked to rate series of statements that range from their personal view of workplace culture, social support and motivation. The results of the study verify it is vital for organization to critically reevaluate and improvise the firm’s policy, process and standard operating procedure that encapsulate the balance between employee’s work and hours outside the workplace. For future research the researcher suggest to add more dimensions of work-life balance and to widen the group pf the populations for more rigorous findings.